2018
DOI: 10.5194/acp-18-16419-2018
|View full text |Cite
|
Sign up to set email alerts
|

The size-resolved cloud condensation nuclei (CCN) activity and its prediction based on aerosol hygroscopicity and composition in the Pearl Delta River (PRD) region during wintertime 2014

Abstract: Abstract. A hygroscopic tandem differential mobility analyzer (HTDMA), a scanning mobility cloud condensation nuclei (CCN) analyzer (SMCA), and an Aerodyne high-resolution time-of-flight aerosol mass spectrometer (HR-ToF-AMS) were used to, respectively, measure the hygroscopicity, condensation nuclei activation, and chemical composition of aerosol particles at the Panyu site in the Pearl River Delta region during wintertime 2014. The distribution of the size-resolved CCN at four supersaturations (SSs of 0.1 %,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 63 publications
4
49
4
Order By: Relevance
“…The two cases were chosen to represent two typical convection systems with moderate and strong convective strength, respectively. For each cloud system, we perform a baseline experiment with four numerical simulations in which the number concentrations of aerosols (here confined to be hygroscopic particles with diameter > 0.1 μm that could serve as CCN under favorable supersaturation) are 100, 600, 1600, and 3200 cm −3 , covering clean to polluted conditions 38 40 . In each simulation, the average INP fraction is estimated to be about 1/20000, based on heterogeneously nucleated ice number concentration predicted dynamically and the total aerosol concentration initialized in our simulations.…”
Section: Resultsmentioning
confidence: 99%
“…The two cases were chosen to represent two typical convection systems with moderate and strong convective strength, respectively. For each cloud system, we perform a baseline experiment with four numerical simulations in which the number concentrations of aerosols (here confined to be hygroscopic particles with diameter > 0.1 μm that could serve as CCN under favorable supersaturation) are 100, 600, 1600, and 3200 cm −3 , covering clean to polluted conditions 38 40 . In each simulation, the average INP fraction is estimated to be about 1/20000, based on heterogeneously nucleated ice number concentration predicted dynamically and the total aerosol concentration initialized in our simulations.…”
Section: Resultsmentioning
confidence: 99%
“…The average κ values, reported by previous studies, were generally found to be in the range of 0.30-0.35; however, CCN activities could be significantly reduced if measurement sites were affected by fresh urban pollution or biomass burning (Rose et al, 2010;Gunthe et al, 2011;Zhang et al, 2014;Wu et al, 2017) due to enhanced contribution of soot and organics. We note that a few recent studies (Atwood et al, 2017;Zhang et al, 2017;Cai et al, 2020) also reported higher aerosol hygroscopicity, as shown in Table S5. For example, the average κ values observed at the Xinzhou site (Zhang et al, 2017) appeared to be larger than those reported at other continental sites probably because aerosols arriving at this site were heavily aged; in addition, two studies which investigated aerosol CCN activities in the marine boundary layer reported larger κ values (Atwood et al, 2017;Cai et al, 2020) compared to those at continental sites.…”
Section: Discussionmentioning
confidence: 52%
“…Under marine background conditions, the average κ a values were determined to be 0.65±0.11 and 0.46±0.17 for the accumulation and Aitken modes (Atwood et al, 2017). Compared to marine background conditions, CCN activities were reduced after extensive precipitation, with average κ a values determined to be 0.54±0.14 and 0.34±0.11 for the accumulation and Aitken modes, whereas during periods impacted by biomass burning, κ a values were reduced to 0.40±0.03 for the accumulation mode but increased instead to 0.56 ± 0.25 for the Aitken mode (Atwood et al, 2017 (Cai et al, 2020), and no obvious dependence of κ a on particle size (50-100 nm) was observed. The campaign-averaged κ was determined to be ∼ 0.40 (Cai et al, 2020), larger than these measured in the PRD region but smaller than those measured over remote marine regions.…”
Section: Other Locationsmentioning
confidence: 95%
“…The tandem differential mobility analyzer (TDMA) inversion algorithm (Gysel et al, 2009) was applied to calculate the Probability Density Function of GF (GF-PDF). More details about this system can be referred to Cai et al (2018) and Hong et al (2018).…”
Section: Gf=mentioning
confidence: 99%